A Brief Historiography of African Economic History - Maliehe, Sean; Justus Liebig University Giessen (My University, 2021)
The paper recalls the long history of colonial exclusion of African perspectives from economic history. The struggle for the recognition of local perspectives is not only part of the fight for democracy, but essential precondition for science to overcome power related distortions of truth.
Keywords: economic history; Africa; postcolonialism; democracy; ddc:900